The FAST‐M complex intervention for the detection and management of maternal sepsis in low‐resource settings: a multi‐site evaluation. (3rd March 2021) - Cheshire, J; Jones, L; Munthali, L; Kamphinga, C; Liyaya, H; Phiri, T; Parry‐Smith, W; Dunlop, C; Makwenda, C; Devall, AJ; Tobias, A; Nambiar, B; et al.
Abstract : Objective: To evaluate whether the implementation of the FAST‐M complex intervention was feasible and improved the recognition and management of maternal sepsis in a low‐resource setting. Design: A before‐and‐after design. Setting: Fifteen government healthcare facilities in Malawi. Population: Women suspected of having maternal sepsis. Methods: The FAST‐M complex intervention consisted of the following components: the FAST‐M maternal sepsis treatment bundle and the FAST‐M implementation programme. Performance of selected process outcomes was compared between a 2‐month baseline phase and 6‐month intervention phase with compliance used as a proxy measure of feasibility. Main outcome result: Compliance with vital sign recording and use of the FAST‐M maternal sepsis bundle. Results: Following implementation of the FAST‐M intervention, women were more likely to have a complete set of vital signs taken on admission to the wards (0/163 [0%] versus 169/252 [67.1%], P < 0.001). Recognition of suspected maternal sepsis improved with more cases identified following the intervention (12/106 [11.3%] versus 107/166 [64.5%], P < 0.001). Sepsis management improved, with women more likely to receive all components of the FAST‐M treatment bundle within 1 hour of recognition (0/12 [0%] versus 21/107 [19.6%], P = 0.091). In particular, women were more likely to receive antibiotics (3/12 [25.0%] versus 72/107 [67.3%], P = 0.004) within 1 hour of recognition of suspected sepsis. Conclusion: Implementation of the FAST‐M complex intervention was feasible and led to the improved recognition and management of suspected maternal sepsis in a low‐resource setting such as Malawi. Tweetable Abstract: Implementation of a sepsis care bundle for low‐resources improved recognition & management of maternal sepsis. Tweetable Abstract: Implementation of a sepsis care bundle for low‐resources improved recognition & management of maternal sepsis. This article includes Author Insights, a video abstract available at https://vimeo.com/bjog/authorinsights16658